Churchless : understanding today's unchurched and how to connect with them : based on surveys by Barna Group - Barna, George; Barna Group (Carol Stream, IL : Tyndale House Publishers, Inc., 2014)
Churchless presents the startling trends reveled by two decades of Barna Group interviews with thousands of churchless men and women, and offers discerning analysis of the results from bestselliing authors George Barna (Revolution) and David Kinnaman (You Lost Me). This practical, insight-driven book will help you look past the surface of church attendance to deeper spiritual realities and understand those who choose not to be part of a church - the first step toward building trust-based relationships that lead to Christ-centered community. -- Book Jacket
Is churchlessness a crisis? Why people leaving churches matters to the church -- Our cultural moment. What is different about our time -- Profiling the unchurched. Demographics and self-descriptions of churchless people -- Perceptions of faith, Christianity, and churches. What unchurched people think and feel about religion -- Doing faith. The religious behaviors of churchless people -- The creed of the creedless. The religious beliefs that define unchurched people's faith -- Born again and unchurched. The paradox of trusting Christ but not the local church -- Disengaged and dropping out. Understanding the reasons people choose to leave church life -- The intersection of family and faith. Family life among unchurched people -- The ideals that propel the unchurched forward. The goals, morals, and values at the heart of churchless adults -- This is how they roll. The lifestyle choices and activities of the unchurched -- Reaching the skeptics. Atheists and agnostics are a different brand of unchurched people -- Faith, future tense. The faith experience and spiritual jourrney unchurched adults are seeking -- Why churches matter. Advocating for church in a post-Christian culture -- Appendix 1: About the research -- Appendix 2: About Barna Group -- Appendix 3: Glossary of terms -- Acknowledgments -- Endnotes.
Includes bibliographical references.
Keywords: Non-church-affiliated people; Evangelistic work